IDENTIFIKASI KEBERBAKATAN CABANG OLAHRAGA BOLA VOLI - Purba, Ari; Supriatna, Eka; Samodra, Y. Touvan Juni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aimed to determine whether there were talented students in volleyball. The study was conducted in 4 elementary schools from 4 districts in Kuburaya Regency. This research was a quantitative study with a descriptive survey. The population in this study were 8 years old students above and from 4 elementary schools with a total sample of 160 male and female students. The instrument used was the tool in the sport search method with 10 test items. Data analysis techniques was using Australian sport search. The results of the talented survey using the sport search method in 4 elementary schools showed the results (10%) of students were very talented, (8.125%) students were quite talented, and (81.875%) students were less talented, in volleyball. The results of the study showed that there were many students who were less talented in volleyball compared to those who were very gifted.Keywords: Identifcation, Talented, Volleyball Sports.